Adsorption of H2O and dimethyl carbonate at high pressure over zeolite 3A in fixed bed column - Bruno A. V. Santos (2014)
The adsorption of dimethyl carbonate (DMC) and water over zeolite 3A-at high pressure conditions (20 MPa) using a mixture of CO2 and methanol as solvent-was studied by the analysis of pulse responses in a fixed bed column. The enthalpies of adsorption of water (-25 +/- 5 kJ.mol(-1)) and DMC (-20 +/- 6 kJ.mol(-1)) were determined from the experimental data at 313 K, 333 K, and 353 K; a selectivity for water/DMC around 2 was observed in the range studied. Furthermore, a mathematical model to describe the pulse response, considering linear adsorption, axial dispersion, and linear driving force for mass transfer, was developed to estimate the global mass transfer coefficients by fitting the experimental data: 1.9 x 10(-5) to 2.8 x 10(-5) m.s(-1) for DMC and 2.8 x 10(-5) to 3.9 x 10(-5) m.s(-1) for water. Several correlations to predict the axial dispersion and the global mass transfer coefficients were compared, showing good agreement with the values estimated experimentally.